Lipopeptide surfactin ameliorates the cell uptake of platensimycin and enhances its therapeutic effect on treatment of MRSA skin infection. (15th July 2022) - Xiong, Yi; Kong, Jieqian; Yi, Sirun; Tan, Qingwen; Bai, Enhe; Ren, Nan; Huang, Yong; Duan, Yanwen; Zhu, Xiangcheng
Abstract: Objectives: The rapid development of drug-resistant bacteria, especially MRSA, poses severe threats to global public health. Adoption of antibiotic adjuvants has proved to be one of the efficient ways to solve such a crisis. Platensimycin and surfactin were comprehensively studied to combat prevalent MRSA skin infection. Methods: MICs of platensimycin, surfactin or their combinations were determined by resazurin assay, while the corresponding MBCs were determined by chequerboard assay. Growth inhibition curves and biofilm inhibition were determined by OD measurements. Membrane permeability analysis was conducted by propidium iodide staining, and morphological characterizations were performed by scanning electron microscopy. Finally, the therapeutic effects on MRSA skin infections were evaluated in scald-model mice. Results: The in vitro assays indicated that surfactin could significantly improve the antibacterial performance of platensimycin against MRSA, especially the bactericidal activity. Subsequent mechanistic studies revealed that surfactin not only interfered with the biofilm formation of MRSA, but also disturbed their cell membranes to enhance membrane permeability, and therefore synergistically ameliorated MRSA cellular uptake of platensimycin. Further in vivo assessment validated the synergistic effect of surfactin on platensimycin and the resultant enhancement of therapeutical efficacy in MRSA skin-infected mice. Conclusions: The combination of effective and biosafe surfactin and platensimycin could be a promising and efficient treatment for MRSA skin infection, which could provide a feasible solution to combat the major global health threats caused by MRSA.